A methods engineering study on Jianelie's Garments - De Leon, Salve Regina; Magtoto, Antonio; Santos, Rowel; Tappa, Milette (Quezon City College of Engineering, University of the Philippines Diliman, 2002)
Methods Engineering aims to improve existing operations systems to raise productivity and lower costs. The company chosen for the study is Janelles's Garments, a subcontractor of Freego Jeans and Paddocks Jeans. It is currently experiencing setbacks from production delays. Documentation of the company and the processes were done to familiarize the researchers with the system. Several Analytical tools were utilized to come up with the feasible solution to the problem that caused the setbacks. These tools are the following: Process Charting for Operation Analysis, Stream Diagnostic Charting and Ishikawa Diagram for Problem Analysis and finally, Decision Analysis for the choice of problems and feasible alternatives. All alternatives drawn were products of Methods Engineering. Problems that can not be addressed by ME were not included in the study. The group established three major causes of production delay: presence of work-in-process in the work area, reworks and threads shortage. A time study was conducted to quantify the problem. With the proper use of the techniques learned in the course, the group was able to come up with the solutions addressing the three causes of the delay. To prevent thread shortage, buffer stocks should be kept. To avoid unnecessary reworks, machines should be properly maintained and any reworking should be done by the operator without pay. To forestall presence of work-in-process, a suitable materials handling equipment was suggested.
Submitted in partial fulfillment of the course requirements in IE 32 : Methods engineering.
Keywords: Jeans (Clothing); Ready-to-wear clothing industry; Methods engineering